EFFECT ADDITION OF COPPER AND HEAT TREATMENT TEMPERATURE ON MICROSTRUCTURE AND CORROSION RESISTANCE OF NITINOL ALLOY - ILHAM REYHAN (NIM : 12513019), MUHAMMAD
Nitinol is a good alloy to be used as a medical devices, due to its good biocompatibility, especially the corrosion resistance and thrombogenicity. Copper (Cu) has an atomic radius similar to the radius of a nickel atom and a crystal structure similar to that of nickel so that the addition of copper to 30% Cu may substitute nickel in an intermetallic NiTi alloy while maintaining the temperature of the austenitic phase transformation. A series of experiments were conducted to study the effect of adding Copper elements on nitinol alloys to microstructure and corrosion resistance. Aging was performed on a horizontal tube furnace at a temperature of 550oC and 650oC in inert condition and followed by with rapid cooling. The alloy is then characterized by optical microscope, X-Ray Diffractometer, Scanning Electron Microscope - Energy Dispersive Spectroscopy to determine the microstructure and dispersion of the integrating element. In addition to microstructure analysis, a corrosion resistance test was performed using tafel extrapolation method to determine the corrosion rate. Based on the experiment result, addition of Cu 4-12% resulted in the formation of Ti(Ni, Cu) phase containing Ti2(Ni,Cu) and Ti(Ni,Cu)2 precipitate. The corrosion test results show that 12% copper addition with aging heat treatment at 550oC temperature produces the best corrosion resistance at the rate of 0.002630 mmpy compared to without Copper addition at the same aging temperature at a rate of 0.004183 mmpy.